1999
DOI: 10.1111/j.1572-0241.1999.01212.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori in The Canadian Arctic: Seroprevalence and Detection in Community Water Samples

Abstract: The seroprevalence of H. pylori in the study group was higher than rates in southern Canadian populations, but lower than the seroprevalence previously documented in a Canadian subarctic Indian (First Nations) community. The detection of H. pylori in local water supplies may indicate a natural reservoir for the organism or possible contamination from human sewage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(4 citation statements)
references
References 18 publications
1
2
1
Order By: Relevance
“…This agreed with the findings of Mckeown et al who reported that antibody status did not differ with respect to alcohol [18]. This did not however agree with the findings of Zhang et al who reported an association between the two in Australia.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This agreed with the findings of Mckeown et al who reported that antibody status did not differ with respect to alcohol [18]. This did not however agree with the findings of Zhang et al who reported an association between the two in Australia.…”
Section: Discussionsupporting
confidence: 82%
“…The findings of this study did not also agree with the study by Papiez et al that water-borne transmission of H. pylori could be an important source of infection in developing countries [8]. A study in Guatemala reported that H. pylori was unlikely to be transmitted by water [17] but epidemiological studies in many countries such as China [18], Lima Peru [19], and Colombia [20] had shown that infection was related to H. pylori contaminated water sources. Dube et al also reported that H. pylori could live in tap water in its infectious bacillary form, and in river water for several months in the nonculturable but viable cocoid form.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Mexico (Mazari-Hiriart et al 2001) and Peru (Hulten et al 1996), from water samples taken from a delivery truck in the Canadian Arctic (McKeown et al 1999) and from drinking water storage pots in the Gambia (Bunn et al 2002). A study by Hulten et al (1998) used two PCR assays to examine municipal treated and well water samples from all 25 counties of Sweden for the presence of Helicobacter DNA: 37.5% of wells, 12% of municipal sources and 12% of wastewater samples were found to be positive for Helicobacter DNA.…”
Section: Transmission Of H Pylori In Watermentioning
confidence: 99%